Isolation and characterization of microsatellites in selected Philippine native and endemic Gobiidae species - Punongbayan, Aprill S.; Diaz, Ma. Genaleen Q.; Bulasag, Abriel S.; Reamillo, Ma. Cecilia S.; Ocampo, Pablo P. (2011)
Microsatellite markers enable species and parentage identification, assessment of genetic diversity and population genetic structure, determine relationships between populations and species are widely used in marker-assisted breeding. These highlight the significance of the isolation, characterization, and development of microsatellite markers from our own, Philippine endemic and native freshwater fishes. Five Philippine native and endemic Gobiidae species were collected. These include Glossogobius celebius, G. giuris, Rhinogobius sp., Gobiopterus lacustris, and Mistichthys luzonensis. A modified protocol for the construction of microsatellite enriched genomic library was used. Genomic DNAs from each species were pooled, digested with Rsa1, size-selected, purified and ligated to Mlu I adaptors. DNA containing microsatellite fragments were captured by biotinylated oligo probes [(TC)10, (CA)10, and (TG)10] and recovered using streptavidin magnetic particles. After PCR, the product was ligated to pGEM-T Easy vector, transformed into JM109 competent cells and plated on Luria-Bertani (LB) agar medium. Recombinant plasmids identified through blue-white screening were sequenced. However, there was low efficiency. To increase efficiency in selecting clones containing microsatellites, more stringent hybridization procedures are now being explored including the hybridization of colonies with non-radioactively labelled repeat oligonucleotides.
Keywords: Gobiidae; microsatellites